Prognostic biomarkers in patients with human immunodeficiency virus‐positive disease with head and neck squamous cell carcinoma. Issue 12 (25th September 2017) - Zhang, Hongzheng; Kim, Sungjin; Chen, Zhengjia; Nannapaneni, Sreenivas; Chen, Amy Y.; Moore, Charles E.; Sica, Gabriel; Mosunjac, Marina; Nguyen, Minh Ly T.; D'Souza, Gypsyamber; Carey, Thomas E.; Peterson, Lisa A.; et al.
Abstract: Background: We examined the prognostic value of a panel of biomarkers in patients with squamous cell carcinoma of the head and neck (SCCHN) who were human immunodeficiency virus (HIV) positive (HIV‐positive head and neck cancer) and HIV negative (HIV‐negative head and neck cancer). Methods: Tissue microarrays (TMAs) were constructed using tumors from 41 disease site‐matched and age‐matched HIV‐positive head and neck cancer cases and 44 HIV‐negative head and neck cancer controls. Expression of tumor biomarkers was assessed by immunohistochemistry (IHC) and correlations examined with clinical variables. Results: Expression levels of the studied oncogenic and inflammatory tumor biomarkers were not differentially regulated by HIV status. Among patients with HIV‐positive head and neck cancer, laryngeal disease site ( P = .003) and Clavien‐Dindo classification IV (CD4) counts <200 cells/μL ( P = .01) were associated with poor prognosis. Multivariate analysis showed that p16 positivity was associated with improved overall survival (OS; P < .001) whereas increased expression of transforming growth factor‐beta (TGF‐β) was associated with poor clinical outcome ( P = .001). Conclusion: Disease site has significant effect on the expression of biomarkers. Expression of tumor TGF‐β could be a valuable addition to the conventional risk stratification equation for improving head and neck cancer disease management strategies.